Text, image, and otherness in children's Bibles : what is in the picture? - Vander Stichele, Caroline; Pyper, Hugh S. (Semeia studies, 2012)
"Children's Bibles are often the first encounter people have with the Bible, shaping their perceptions of its stories and characters at an early age. The material under discussion in this book not only includes traditional children's Bibles but also more recent phenomena such as manga Bibles and animated films for children. The book highlights the complex and even tense relationship between text and image in these Bibles, which is discussed from different angles in the essays. Their shared focus is on the representation of 'others' foreigners, enemies, women, even children themselves in predominantly Hebrew Bible stories. The contributors are Tim Beal, Ruth B. Bottigheimer, Melody Briggs, Rubn R. Dupertuis, Emma England, J. Cheryl Exum, Danna Nolan Fewell, David M. Gunn, Laurel Koepf, Archie Chi Chung Lee, Jeremy Punt, Hugh S. Pyper, Cynthia M. Rogers, Mark Roncace, Susanne Scholz, Jaqueline S. du Toit, and Caroline Vander Stichele"--Publisher description